2020
DOI: 10.1101/2020.04.08.20058578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Possible Role of Vitamin D in Suppressing Cytokine Storm and Associated Mortality in COVID-19 Patients

Abstract: Objectives To investigate the possible role of Vitamin D (Vit D) deficiency via unregulated inflammation in COVID-19 complications and associated mortality. Design The time-adjusted case mortality ratio (T-CMR) was estimated as the number of deceased patients on day N divided by the number of confirmed cases on day N-8. The adaptive average of T-CMR (A-CMR) was further calculated as a metric of COVID-19 associated mortality in different countries. A model based on positivity change (PC) and an estimated prev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
211
1
20

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(238 citation statements)
references
References 52 publications
6
211
1
20
Order By: Relevance
“…Some preliminary studies have demonstrated that Vitamin D status and sun exposure are important factors to consider for reducing the rates of transmission, infection, and severity of illness. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Some preliminary studies have demonstrated that Vitamin D status and sun exposure are important factors to consider for reducing the rates of transmission, infection, and severity of illness. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Although controversial, the effect of vitamin D deserves further study because it seems to have a positive result against this type of infection (Kakodkar et al 2020). Laird et al (2020) suggest a positive relation between immune system and vitamin D regulating cytokine response to pathogens, fact con rmed by Daneshkhah et al (2020) Another factor in uencing the COVID-19 epidemic behavior in Mexico could be the vaccination scheme. Recently, researchers have suggested that Bacillus Calmette-Guérin (BCG) vaccination against tuberculosis could diminish the spread of COVID-19 (Gupta 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In older individuals, NLRP3 may be poised for hyperactivation by SARS-CoV-2 components 25 . Elimination of severe vitamin D deficiency reduces the risk of high CRP levels (odds ratio of 2) which may be used as a surrogate marker of cytokine storm 44 . Vitamin D inhibits NLRP3 activation by impeding its deubiquitination mediated by BRCC3 45 .…”
Section: Figure 1 Ccfr Is Significantly Higher In Countries With Higmentioning
confidence: 99%